2018
DOI: 10.1055/a-0743-5386
|View full text |Cite
|
Sign up to set email alerts
|

Single-operator cholangioscopy for diagnosis of cholangioadenoma (bile duct adenoma) and its potential impact on surgical management

Abstract: Background and study aims  Cholangioadenoma is not recognized commonly and is often only diagnosed on surgical specimens. Direct per oral single-operator cholangioscopy (SOC) allows characterization of common bile duct (CBD) lesions through direct visualization and directed forceps biopsies with potential for impacting surgical management decisions. This is a retrospective review of all SOC cases diagnosed with cholangioadenoma. Patient demographics and outcomes were recorded. Three patients (all male), averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…(II) Intrahepatic cholangiocarcinoma: uneven signal, often accompanied by shrinkage of the adjacent liver capsule, atrophy of the hepatic lobes at the distal end of the lesion, and dilatation of the intrahepatic bile duct. The dynamic enhancement manifested as mild and moderate peripheral enhancement in the early stage, and progressive and concentric strengthening in the later stage ( 17 , 18 ). (III) Metastatic tumors: having a history of malignant tumors in other parts, generally multiple, varying in size, enhanced with ring-shaped enhancement, and partially with “bull’s eye sign” ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…(II) Intrahepatic cholangiocarcinoma: uneven signal, often accompanied by shrinkage of the adjacent liver capsule, atrophy of the hepatic lobes at the distal end of the lesion, and dilatation of the intrahepatic bile duct. The dynamic enhancement manifested as mild and moderate peripheral enhancement in the early stage, and progressive and concentric strengthening in the later stage ( 17 , 18 ). (III) Metastatic tumors: having a history of malignant tumors in other parts, generally multiple, varying in size, enhanced with ring-shaped enhancement, and partially with “bull’s eye sign” ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, direct cholangioscopy has emerged as a valuable tool offering both diagnostic and therapeutic benefits that can guide surgical management [ 5 ]. Eccles et al reported a case series demonstrating the utility of cholangioscopy, where synchronous CBD cholangiocarcinoma and hilar cholangioadenoma were identified, altering surgical management based on findings not visualized in prior imaging studies [ 6 ]. A literature review by Loh et al identified 39 cases of BDAs, with the majority diagnosed via surgical specimens, and only a limited number of cases diagnosed based on biopsies obtained through direct cholangioscopy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Only few series evaluated the role of POCS to diagnose protruding biliary lesions. 3,4 Since its introduction in 1970, cholangioscopy gained progressive attention. 5 While the mother-baby system was heavily burdened by the fragility of the scope, the poor quality of the images and the inconvenience of requiring two operators, the novel peroral cholangioscope (SpyGlass DS, Boston Scientific, USA) is currently a feasible single-operator instrument for high-resolution visualization of the biliary tree.…”
Section: Discussionmentioning
confidence: 99%